PENGEMBANGAN TELEMONITORING PADA PULSE OXIMETER MENGGUNAKAN SPO2 NELLCOR BERBASIS INTERNET OF THINGS - Kuspranoto, Abdul Haris; Nuha ABA, Muhammad Ulin (MEDIKA TRADA : Jurnal Teknik Elektomedik Polbitrada, 2023)
Telemonitoring is a method of long-distance health services using information technology to provide data to health services. Telemonitoring can save time, costs and effectiveness of health services. The biggest challenge in using Telemonitoring is that the adoption rate is still low and there has not been much development in medical equipment. Pulse Oximeter Using Nellcor SpO2 Based on the Internet of Things, functions to measure oxygen saturation (SpO2) and measure heart rate remotely. Then the results can be monitored via an Android smartphone application by utilizing an internet connection. To make this happen, hardware and software planning was made. This module uses a Nellcor SpO2 sensor which will regulate SpO2 and Heart Rate values ​​in the range of 60-100%. This microcontroller module uses ESP32 which will act as the brain of the device controller and connect the device to an Android smartphone. The measurement results of this tool are tampilaned on a 3.5 inch Nextion LCD and the Inventor application on an Android smartphone. The difference between oxygen saturation and heart rate readings on the Prosim 8 device has the largest error percentage of 5.4% for heart rate and the smallest at 0% for SpO2. This application can record SPO2 data and falling heart rate on patients periodically, so that their condition and condition can be monitored. for diagnostic data on patients remotely.